Impact of filament denier on functional performance of microfiber in situ bags - Doaa Elgohary Hanafy; Dina Mohamed Hamoda; Ibrahim Mohamed Khattab; Ahmed Abdelkader Aboamer (Acta Scientiarum. Animal Sciences, 2020)
In situ bags made from microfiber fabrics have a greater surface area and filtration efficiency that retains the fine particles and reduce the variation in the results. Also, it is more durable than that made from traditional fabrics. This work aimed to study the effect of filament denier on the performance of in situ bags. Two polyester microfilaments with 0.4 and 0.7 deniers were used in manufacturing of four fabrics. Physical and mechanical properties of manufactured fabrics were measured before and after incubation to show the efficiency of the manufactured samples. In vitro trail was conducted to estimate ruminal degradability after 24 and 48 hours for three feedstuffs using three cannulated rams as replicates. The mechanical properties of manufactured in situ bags were significantly affected with both denier per filament and weft densities. According to the statistical analysis of radar chart, sample 2 remarked the highest value which achieved the acceptable ruminal dry matter disappearance compared with Ankom bags in different incubation times.